2015
DOI: 10.1002/j.0022-0337.2015.79.11.tb06029.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Students’ Dental Admission Test Scores and Performance on a Dental School's Competency Exam

Abstract: The aim of this study was to investigate whether there was a statistically signiicant positive correlation between dental students' Dental Admission Test (DAT) scores, particularly on the Perceptual Ability Test (PAT), and their performance on a dental school's competency exam. Scores from the written and clinical competency exam administered in the fall quarter of the fourth year of the curriculum at Midwestern University College of Dental Medicine-Arizona were compared to DAT scores of all 216 members of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…In an additional study, DAT Perceptual Ability Test (DAT PAT) scores were found to be weakly linked to success on the Comprehensive Basic Science Examination (CBSE), taken by students applying to oral surgery residency programs 6 . The DAT PAT has also been linked to success in preclinical operative coursework, 7 and an analysis of performance on a clinical competency exam connected DAT PAT to clinical performance 8 . DAT Total Science (DAT TS) scores have also been found to be associated with success in oral pathology coursework 9 .…”
mentioning
confidence: 98%
“…In an additional study, DAT Perceptual Ability Test (DAT PAT) scores were found to be weakly linked to success on the Comprehensive Basic Science Examination (CBSE), taken by students applying to oral surgery residency programs 6 . The DAT PAT has also been linked to success in preclinical operative coursework, 7 and an analysis of performance on a clinical competency exam connected DAT PAT to clinical performance 8 . DAT Total Science (DAT TS) scores have also been found to be associated with success in oral pathology coursework 9 .…”
mentioning
confidence: 98%
“…However, Park et al found those same cognitive factors showed no statistical significance in a cohort of Harvard School of Dental Medicine DMD students 4 . While studies have found a predictive role for PAT scores with preclinical and clinical success, 5 7 others found inconsistency, especially among cohorts with scores of narrow range and high mean 4 , 8 …”
mentioning
confidence: 99%
“…These findings led the authors to speculate that possibly the “strong emphasis placed on an applicant's ability to demonstrate perceptual ability or hand skills prior to dental school is unfounded. Perhaps students are able to develop sufficient manual dexterity while in dental school.” Carroll and Schuster compared DAT scores to performance on a fourth‐year competency exam that consisted of three written sections testing patient assessment and treatment planning, periodontics, and prosthodontics and three clinical patient care sections involving endodontics, operative dentistry, and periodontics 3 . They found the PAT component score of the DAT was the only statistically significant predictor (p<0.05) of clinical performance at their school.…”
mentioning
confidence: 99%